Neural Network Method for Dielectric Optical Coating Design - Chattopadhyay, Utsa; Carstens, Florian; Wienke, Andreas; Hartl, Ingmar; Ay, Nihat; Heyl, Christoph; Tünnermann, Henrik (EPJ Web of conferences, 2024)
We use neural networks to address the challenge of deriving dielectric coating designs from the desired optical properties. We show that our trained neural network can automatically design common laser mirror coatings types efficiently.